Building Critical Awareness Through HIV and AIDS Management Policy at Subdistrict and Village Level (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
The number of PLWHA in Jember Regency has been increasing every year from 2004 to 2016 always, hence HIV/AIDS prevention must involve the community, not just relying on programs from the Department of Health or KPAD. Jember Regent’s policy on HIV/AIDS Management Team at Subdistrict and Village Level strategically involve all components of the society. Society’s participation was not limited to physical participation but extended to critical awareness. This is a descriptive analytic study about logical thinking on fostering critical awareness on HIV/AIDS through subdistrict and village HIV/AIDS team regulated by Jember’s Regent. Policy analysis was done through Triangle of Policy Analysis theory which includes: context, content, process and actors. The result showed that Jember Regent’s policy on HIV/AIDS prevention teams at subdistrict and village level was very effective to foster community’s critical awareness in HIV/AIDS preventive programs at Jember Regency.